Clinical Significance of Volume Status in Body Composition and Physical Performance Measurements in Hemodialysis Patients - Kim, Jun Chul; Do, Jun Young; Kang, Seok Hui (Frontiers in Nutrition, 2022)
Introduction: This study aimed to evaluate the association between volume status and body composition or physical performance measurements in hemodialysis (HD) patients. Methods: A total of 84 patients were enrolled in the study. The participants were divided into tertiles based on the edema index (extracellular water/total body water): low, middle, and high tertiles. Serum albumin and serum hs-CRP levels were measured. The appendicular lean mass index (ALM/Ht2, kg/m2) was measured using dual-energy X-ray absorptiometry. The thigh muscle area index (TMA/Ht2, cm2/m2) was measured using computed tomography. Extracellular and total body water, and phase angles were obtained using bioimpedance analysis. The results of the subjective global assessment (SGA), hand-grip strength (HGS), gait speed (GS), short physical performance battery (SPPB), 30-second sit-to-stand (STS30) test, timed up and go (TUG), sit-to-stand test performed five times (STS5), and 6-minute walk (6-MW) tests were also evaluated. Results: On univariate analysis, the SGA score and phase angle in the high tertile group were the lowest among the three groups. On multivariate analysis, TMA/Ht2 and phase angle in the high tertile were the lowest among the three groups. Inverse correlations were observed between edema index and TMA/Ht2, SGA score, phase angle, HGS, GS, SPPB, STS30, or 6-MW. Positive correlations were observed between the edema index and the STS5 or TUG test. The sensitivity and specificity for predicting low GS were 34.5%, and 89.7%, respectively. The values for predicting low SPPB were 68.0% and 79.7%, respectively. Conclusion: Our study demonstrates that high volume status may be associated with decreased muscle mass and physical performance regardless of inflammatory or nutritional status.